SCHOOL GARDENS AS A TOOL FOR TRANSFORMATION: SUSTAINABILITY AND EMPOWERMENT IN EARLY CHILDHOOD FROM THE PERSPECTIVE OF MICHEL THIOLLENT'S ACTION RESEARCH - Cristina Boufleuher Vergutz , Paula; Ramão Villalva F’ilhi , Mario; José Nicaretta Boufleuher , Davi (Revista Gênero e Interdisciplinaridade, 2026)
The present article addresses the ecological crisis and the urgency of climate issues, positioning Environmental Education (EE) as an essential survival strategy, aligned with the Sustainable Development Goals (SDGs). To promote the necessary paradigm shift, the research is based on the Action-Research methodology, characterized by the close association between investigation and the transformation of reality, aiming at the active involvement of participants in the resolution of collective problems.It is argued that sustainability must begin in Early Childhood, a crucial stage for establishing values, critical thinking, and innate ecological awareness. In this context, the Organic School Garden project is presented as a strategic initiative that addresses Food and Nutritional Security (FNS) laws, by producing fresh and healthy food and promoting food autonomy.The practice of organic cultivation in the school environment contributes to sustainability in a concrete way. It is concluded that, by applying Action-Research, Early Childhood Education empowers children as agents of change, teaching them that food production and sustainability are daily and achievable practices, essential for building a more resilient future.